Methodological Transformations in Contemporary Islamic Studies: Trends, Challenges, and Future Directions - Annaprimadonita (Yayasan Sinergi Kawula Muda, 2024)
This narrative review examines recent methodological developments in Islamic Studies, focusing on how traditional epistemologies intersect with contemporary research practices. The study aims to analyze key innovations and contextual influences shaping the evolution of methodology in education, finance, exegesis, and environmental ethics. Literature was collected from multiple academic databases including Scopus, SpringerLink, Google Scholar, and Web of Science using targeted keywords such as